Necrotizing autoimmune myopathy: a case series - Sulaiman Sahari, Narisa; Marwan, Abdul Aziz; Suahilai, Dayang Masyrinartie; Mohd Jamid, Nurulraziquin; Shahril, Nor Shuhaila (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2020)
Necrotizing autoimmune myopathy (NAM) is considered a new subgroup of a rare autoimmune idiopathic inflammatory myopathies. Classically, NAM presented with sub-acute onset of proximal muscle loss of power with raised creatinine kinase and characteristic muscle biopsy showing muscle necrosis and regeneration with little inflammation. Statin use, connective tissue diseases, malignancy and HIV infection are the identified risk factors for NAM. The autoantibodies expected to be presented in NAM are anti-signal recognition particle (SRP) and anti-hydroxymethylglutaryl-coenzyme A reductase (anti-HMGCR) antibodies. In this article, we present three cases of NAM with different risk factors and autoantibodies which we believe to have impact on the clinical course and outcome of our patients.